TGFβ2 differentially modulates smooth muscle cell proliferation and migration in electrospun gelatin-fibrinogen constructs. (January 2015) - Ardila, Diana C.; Tamimi, Ehab; Danford, Forest L.; Haskett, Darren G.; Kellar, Robert S.; Doetschman, Tom; Vande Geest, Jonathan P.
Abstract: A main goal of tissue engineering is the development of scaffolds that replace, restore and improve injured tissue. These scaffolds have to mimic natural tissue, constituted by an extracellular matrix (ECM) support, cells attached to the ECM, and signaling molecules such as growth factors that regulate cell function. In this study we created electrospun flat sheet scaffolds using different compositions of gelatin and fibrinogen. Smooth muscle cells (SMCs) were seeded on the scaffolds, and proliferation and infiltration were evaluated. Additionally, different concentrations of Transforming Growth Factor-beta2 (TGFβ2) were added to the medium with the aim of elucidating its effect on cell proliferation, migration and collagen production. Our results demonstrated that a scaffold with a composition of 80% gelatin-20% fibrinogen is suitable for tissue engineering applications since it promotes cell growth and migration. The addition of TGFβ2 at low concentrations (≤1 ng/ml) to the culture medium resulted in an increase in SMC proliferation and scaffold infiltration, and in the reduction of collagen production. In contrast, TGFβ2 at concentrations >1 ng/ml inhibited cell proliferation and migration while stimulating collagen production. According to our results TGFβ2 concentration has a differential effect on SMC function and thus can be used as a biochemical modulator that can be beneficial for tissue engineering applications.